2013
DOI: 10.5977/jkasne.2013.19.4.508
|View full text |Cite
|
Sign up to set email alerts
|

The CPR Educational Program Effect of Infant CPR Immediate Remediation for Child Care Teachers

Abstract: The purpose of this study was to evaluate the effectiveness of infant CPR (Cardiopulmonary Resuscitation) immediate remediation[LAB2]. Methods: This is a quasi-experimental study with a non-equivalent comparison group pre-post test design. Participants were 73 child care teachers in J district in Seoul. The experimental group (35) received immediate remediation with video learning [LAB3]for infant CPR education and the control group (38) received video learning only. We investigated confidence of infant CPR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
3
2
0
Order By: Relevance
“…However, even in this infant CPR training program that applied the 5-step method, performance ability decreased by about 11% at 6 months after training. A previous study applying immediate remediation to infant CPR education for childcare teachers found that their performance ability decreased by about 24% at 6 months after training [6]. Despite differences in trainees and methods, this study and the previous one [6] obtained the same basic result: the effects of education decreased with time.…”
Section: Chnrsupporting
confidence: 69%
See 3 more Smart Citations
“…However, even in this infant CPR training program that applied the 5-step method, performance ability decreased by about 11% at 6 months after training. A previous study applying immediate remediation to infant CPR education for childcare teachers found that their performance ability decreased by about 24% at 6 months after training [6]. Despite differences in trainees and methods, this study and the previous one [6] obtained the same basic result: the effects of education decreased with time.…”
Section: Chnrsupporting
confidence: 69%
“…A previous study applying immediate remediation to infant CPR education for childcare teachers found that their performance ability decreased by about 24% at 6 months after training [6]. Despite differences in trainees and methods, this study and the previous one [6] obtained the same basic result: the effects of education decreased with time. This finding therefore demonstrates the need for educational refreshers, at least for childcare teachers, healthcare providers, and preservice healthcare providers, such as nursing and medical students, on a timely basis using a differentiated method.…”
Section: Chnrsupporting
confidence: 69%
See 2 more Smart Citations
“…However, some studies have shown that knowledge of first aid management was a predictor of parents' self-efficacy in infant CPR skills ( 25 , 26 ). The present study showed the benefits of SBT combined with didactics corresponding to mastery training as previously reported ( 27 ) and demonstrated the ability of SBT to improve CPR performance even in lay people such as nursery assistants ( 13 , 21 , 28 30 ). This improvement can be observed both with automatically assessment using QCPR device or by observer assessment using CPR checklist.…”
Section: Discussionsupporting
confidence: 89%